I have seen the reason why the factor theorem works:
f(x) = d(x)q(x) + r(x)
If d(x) = (x - a) then
f(a) = 0*q(a) + r(a)
Therefore f(a) = r(a)
However there is no indication that this will not work with equations other than polynomials (f(x) could be sine(x)) so why does this only work on polynomials?
f(x) = d(x)q(x) + r(x)
If d(x) = (x - a) then
f(a) = 0*q(a) + r(a)
Therefore f(a) = r(a)
However there is no indication that this will not work with equations other than polynomials (f(x) could be sine(x)) so why does this only work on polynomials?